Annette L. Juliano, Bronze, Clay and Stone. Chinese Art in the C.C. Wang Family Collection. Publicado por Hsi An T'ang y distribuido por University of Washington Press, Seattle, 1988, 184 pp. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1990)
-